Methods to Explore Changes in the Extent of Habitat Provided by Ceratophyllum demersum Shoots for Epiphytic Organisms in Changing Environments - Kitti Németh; Attila I. Engloner (Ecology and Evolution)
ABSTRACT In aquatic environments, the surface of submerged plants provides extensive habitat for a variety of epiphytic organisms; however, appropriate methods to determine this quantity and its changes related to altering environmental conditions are lacking. In this study, we examined one of the most morphologically complex, worldwide distributed submerged macrophytes, Ceratophyllum demersum. After exploring the morphological diversity of this plant in various aquatic habitats and accurately measuring its total surface area, we proposed methods to easily calculate or estimate this trait, either based on variables that can be recorded in the field without damaging the plants or on data obtained from the literature. The total plant surface area of the examined shoots with an average total length of 73–143 cm and 28–63 internodes was 147–313 cm2; the largest entire plant included in this study had a total surface area of 3352 cm2. The greatest morphological diversity in C. demersum was caused by variability in the number and total length of internodes, while the internodal diameter and the leaf whorl area varied less. The former two variables are easy to determine; the latter two can provide constants for calculations. In addition, strong correlations were revealed between the total surface area and shoot length, as well as fresh weight, allowing easy estimation of plant surface area and its changes in response to a changing environment. As an example, a change in shoot length of 10 cm or fresh weight of 100 g results in a change in total shoot surface of approximately 15 or 5400 cm2. In addition to studies focusing on epiphytic communities, the proposed methods can provide fundamental information for many scientific and practical fields from ecology to phytoremediation and wastewater treatment.